Desmond Doss' Biblical Determination to Defend His Faith in The Hacksaw Ridge Movie - Hana Theresya Nisa; Ahmad Muhid; Eko Heriyanto (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2022)
The film is one of the innovations of drama literary works. There are various types of films. One of them is an action movie that includes war and military action. This type of film is usually famous for bloodshed. Hacksaw Ridge Movie is just the opposite. The main character in this film is a medic soldier who is against killing or touching weapons. This character is the son of a former World War I corporal and a devout Adventist Christian. A devout Christian knows God's word and works on it. It is including the commandments that God said in the Torah. One of God's commands in the Torah in Exodus 20:13 (King James Version) is “Thou shalt not kill.” Bible says that a person who believes in God must be able to faithfully exercise his faith because God is faithful. The main character in this film has the determination to be faithful to his faith. The purpose of this study is to find evidence in the form of data relating to what makes the main character in this film decide not to kill, how he maintains his faith, and what effect he gets from his decision. In conducting this research, the writer uses descriptive methods with data collection are include literature study, observation, and note-taking. The collected data is then analyzed and presented qualitatively. The result showed that the writer found two data which became the strongest reason for the main character not to kill; nine pieces of data that prove how the main character fights for his faith; and eight data that prove the effects of the main character's determination. From this film, the writer can conclude that, if a person has true faith, he should work on that faith faithfully.